The effect of harmonization of tax regulations and tax knowledge on taxpayer compliance at Kpp Pratama Makassar Selatan - Nurwahyuni Nurwahyuni; Muhammad Nuryamin Akbar Khairullah; Muhammad Fardhan Dinarto; Risvina Ridwan; Sarwan Arfah; Kartini Kartini; Nurul Fadillah; Muhammad Ainul Yaqin (Jurnal Riset Perpajakan: Amnesty, 2024)
Harmonization of clearer tax regulations and a better understanding of taxation can result in improvements in taxpayer compliance with tax obligations. This study aims to examine the effect of harmonization of tax regulations and tax knowledge on taxpayer compliance. The data in this study was obtained from taxpayers in Makassar City who were registered with KPP Pratama Makassar Selatan. This study used primary and secondary data by conducting direct research in the field by providing questionnaires/statement sheets to 99 respondents. Data analysis techniques are carried out with descriptive statistical analysis and SPSS (Statistical Program for Social Science). The results showed that harmonization of tax regulations had a positive and significant effect on taxpayer compliance. Knowledge of taxation has a positive and significant effect on taxpayer compliance. Harmonization of tax regulations and knowledge of taxation simultaneously together have a positive and significant effect on taxpayer compliance.